Avaliação em profundidade do Projeto Futsal SESC, uma análise das percepções dos atores sociais nos núcleos das escolas Educar SESC I e II na cidade de Fortaleza - Oliveira, Francisco Antonio Rodrigues (2024)
This study aims to evaluate the effectiveness of the SESC Futsal Program as a tool for the integral development of children and adolescents. It sought to understand the experience of those involved in the program, considering the social and cultural context. To this end, questionnaires and interviews were used with the participants' guardians. The information was organized into thematic axes and analyzed to identify patterns and meanings. A qualitative approach was used to interpret the phenomena in the natural context of the participants, according to the meanings attributed by those involved. Futsal is configured as a powerful tool for promoting social inclusion, through the development of motor and social skills, contributing to the formation of more conscious and engaged citizens. By providing the opportunity to practice sports for children and adolescents from different social backgrounds, SESC contributes to the democratization of access to sports and the reduction of social inequalities. The technical evolution of the students, the acquisition of motor skills, and the impact of futsal on the integral development of the participants are perceptible. By participating in the program, young people develop skills such as teamwork, discipline, respect for differences, and self-esteem, which better prepares them to face life's challenges. Since the research addresses the importance of sports as a tool for social inclusion and transformation, it can be inferred that it has the potential to contribute to the improvement of public policies for sports and leisure. The study reinforces the idea that sports, when practiced in an organized manner and with clear objectives, is a preponderant instrument for the integral human development of vulnerable communities